Evaluation of serum levels Superoxide dismutase in women with polycystic ovarian syndrome and gingivitis - Ali, Omar H.; Raheem, Zainab J.; Imran, Nada K.; Majid, Ali Y.; Ahmed, Maha A.; AL deen Khairi, Azza W. (Journal of Baghdad College of Dentistry, 2018)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine abnormality in women, there is an increasing evidence for an oxidative stress in PCOS that induce genomic and mitochondrial deoxyribonucleic acid damage that leads directly to reduced fertility. The objectives of this study are to assess and compare the periodontal health status by measuring clinical periodontal parameters (PLI, GI and BOP)as well as serum levels of superoxide dismutase at gingivitis ,gingivitis with PCOS and healthy periodontium groups, then correlate between clinical and biochemical parameters. Materials and Methods: 60 females with an age range between (25-40) years old had been tested and divided into3 groups ,the control group consists of (20) females with healthy periodontium, group of (20) females with gingivitis and group of (20) females with gingivitis and PCOS. After completion of clinical periodontal parameters recording (PLI, GI& BOP), blood samples were collected and biochemical analysis of serum samples were carried out by using [Super oxide dismutase Assay kit] to evaluate serum super oxide dismutase levels. Results: The highest mean values of PLI,GI and BOP score1 were found in gingivitis+PCOS group. Highly significant difference was revealed among the groups regarding mean values of Superoxide dismutase with the highest mean value at gingivitis+ PCOS followed by gingivitis groups. Non-significant correlation were demonstrated between clinical and biochemical parameters except the significant moderate positive correlation of BOP at gingivitis+PCOS group. Conclusion: It could be certified that severity of gingivitis may increase in patients with PCOS. The concentration of serum SOD increased with the severity of gingival inflammation as well as the presence of PCOS. Serum SOD may be useful biochemical marker for early detection of periodontal disease and PCOS.